Fire hazards in industry - Thomson, Norman (Butterworth-Heinemann, 2002)
Significant loss to business occurs through fires in the workplace. Whether large or small, fire causes personal suffering, damage to plant, equipment and buildings, and loss of business. Fire legislation has changed over the past few years, especially with the introduction of European Directives. New regulations mean that employers have to carry out fire risk assessment and then, as a result of their findings, put in place control measures to prevent loss of life. Fire Hazards in Industry has been designed to cover, in general terms, exactly what is required of employers. It is written in simple language and considers the basics of good fire safety management. After reading Fire Hazards in Industry, any employer, safety professional or fire safety officer should be able to install a system for carrying out fire risk assessment.-In addition to sections relating to the legal aspects of fire prevention, the book explains the concepts of fire modelling, explosions and combustion reactions. There is also a section relating to common industry fire hazards and hazards associated with electrical equipment. Knowledge of all these topics would be required if a person were to attempt to carry out fire risk assessment. Throughout the book, past case histories are used to illustrate certain aspects of fire and the causes of fire. The cases used have all been published by the Health and Safety Executive as a result of their investigations. These include; Abbeystead, Frodingham steelworks, HMS Glasgow, BP Grangemouth and many more. This book will be equally relevant to motor manufacturing as it is to the chemical industry. There are many case studies included that deal with fire hazards that are found in general industry.-Fire Hazards in Industry is suitable for those who have relatively limited experience in fire safety and therefore use it as part of their career and educational development, but also can be used as reference material for those experienced professionals who have fire safety included in their day to day responsibility.
Includes index.
Keywords: Fire prevention -- Law and legislation.; Fire risk assessment.; Fire prevention -- Management.; elektronické knihy; electronic books